Spotting sporotrichosis skin infection: The first Australian paediatric case series. (15th October 2019) - Schauer, Anna; Campbell, Anita J; Arthur, Ian; Blyth, Chris C; Bowen, Asha C
Abstract : Aim: Sporotrichosis is a dermatomycosis caused by the dimorphic fungus, Sporothrix schenckii, with various outbreaks across Australia attributed to mouldy hay. Our objective was to investigate the clinical presentation and management of cutaneous sporotrichosis in a paediatric population of Western Australia. Methods: A retrospective case review was performed for S. schenckii infections in children below 18 years, between January 2000 and November 2017. Cases were identified from the state‐wide laboratory database and additional clinical data obtained from medical records. Results: Thirty‐two cases of microbiologically proven S. schenckii infection were identified, mostly from rural areas ( n = 20, 63%). Complete clinical data were available for 11 cases (34%). The most common risk factors were exposure to farm animals and hay, arthropod bites and outdoor activities. The median duration from symptom onset to correct diagnosis was 6 weeks (interquartile range: 4–7 weeks). Most cases were initially treated with multiple, broad‐spectrum antibacterial agents ( n = 7, 64%). Targeted therapy (itraconazole) was used in all cases once the diagnosis was made, with a median treatment duration of 5 months (interquartile range: 4–6 months). Morbidity included scarring ( n = 4, 31%), itraconazole associated diarrhoea ( n = 1, 8%) and mild hepatotoxicity ( n = 1, 8%). Conclusion: Summarising the clinical experience of these cases is a useful guide for clinical recognition and may serve to shorten the interval between onset and diagnosis, and avoid the need for antibacterial therapy. These data highlight the importance of recognising Sporotrichosis in children outside an outbreak setting, leading to timely diagnosis and appropriate treatment with antifungal agents.